2001
DOI: 10.1055/s-2001-10622
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Secoiridoid Glucosides in In Vitro Propagated Plants of Gentiana davidii var. formosana by High Performance Liquid Chromatography

Abstract: A simple protocol for in vitro mass propagation of Gentiana davidii var. formosana (Gentianaceae) has been developed. Multiple shoot development was achieved by culturing the stem node explants on Murashige and Skoog (MS) medium supplemented with 4.44 microM N6-benzyladenine (BA). The shoots were multiplied by subculturing on MS medium supplemented with 1.07-10.74 microM alpha-naphthaleneacetic acid (NAA) and 8.88 microM BA. Shoots were rooted on MS basal medium supplemented with various auxins. Shoots rooted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Low shoot multiplication values of G. dinarica were similar to those reported for G. acaulis [3]. For most Gentiana species shoot multiplication requires a somewhat higher, 2.0-2.5 mg l -1 concentration of BA as reported for G. lutea, G. cruciata, G. purpurea, G. acaulis [3], G. kurroo [10], G. davidii [12,13], G. pneumonanthe [21], G. scabra [22], and G. asclepiadea [23]. However, different BA concentrations were recommended even for the same Gentian species, as in case of G. lutea [1].…”
Section: Culture Establishmentsupporting
confidence: 60%
See 1 more Smart Citation
“…Low shoot multiplication values of G. dinarica were similar to those reported for G. acaulis [3]. For most Gentiana species shoot multiplication requires a somewhat higher, 2.0-2.5 mg l -1 concentration of BA as reported for G. lutea, G. cruciata, G. purpurea, G. acaulis [3], G. kurroo [10], G. davidii [12,13], G. pneumonanthe [21], G. scabra [22], and G. asclepiadea [23]. However, different BA concentrations were recommended even for the same Gentian species, as in case of G. lutea [1].…”
Section: Culture Establishmentsupporting
confidence: 60%
“…Conditions for in vitro propagation have also been well defined for G. punctata [7], G. cruciata, G. acaulis and G. purpurea [3,8,9] G. pneumonanthe [2]. In Chinese folk medicine, Gentiana species are considered as important; therefore, Asian species have also been well investigated (G. kurroo [10]; G. tibetica [11]; G. davidii [12,13]). Many varieties of G. triflora have been investigated due to their ability to flower under in vitro culture conditions [14,15] and their differences in ploidy levels [16].…”
Section: Introductionmentioning
confidence: 99%
“…29) BA alone or in combination with NAA in the MS basal medium has been used for the in vitro induction of shoots in the medicinal plants Aconitum carmichaeli, 23) Gentiana scabra, 25) Wasabia japonica, 30) and Gentiana davidii. 31) In preliminary studies, we tested leaf segments, internode segments, and nodes for the induction of shoots. However, no shoot formation in leaf and internode segments was observed (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The biosynthesis of secoiridoids in Gentianaceae plants can be related to the physiological development stage which is affected by plant age, physiology and growing environment of the plant (Piatczak et al 2006;Zhang et al 2010). Chueh et al (2001) reported that the content of gentiopicroside and swertiamarin in the aerial and underground parts of G. davidii var. formosana varied with the age of the in vitro plant.…”
Section: Pcr Analysis Of Transgenic Hairy Rootsmentioning
confidence: 99%